2018
DOI: 10.1002/art.40662
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Gout Among Patients With Sleep Apnea: A Matched Cohort Study

Abstract: In this study, patients with OSA continued to be at higher risk of developing gout beyond the first year following the diagnosis. Our results further indicate that peak incidences of gout vary according to BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 31 publications
1
15
1
3
Order By: Relevance
“…The absence of an overall association between OSA and gout in our study contrasts with a 1.5-fold increased risk of gout with OSA that was reported by two previous studies [4,9] which had used the same data source, i.e., the CPRD GOLD database, or a data source (THIN) that partly overlaps with CPRD [19]. Table 3 shows that this difference can be largely explained by more comprehensive statistical adjustment for potential confounding in the current study, in particular for renal impairment, as measured by eGFR and READ codes, and heart failure.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The absence of an overall association between OSA and gout in our study contrasts with a 1.5-fold increased risk of gout with OSA that was reported by two previous studies [4,9] which had used the same data source, i.e., the CPRD GOLD database, or a data source (THIN) that partly overlaps with CPRD [19]. Table 3 shows that this difference can be largely explained by more comprehensive statistical adjustment for potential confounding in the current study, in particular for renal impairment, as measured by eGFR and READ codes, and heart failure.…”
Section: Discussioncontrasting
confidence: 99%
“…Two prospective studies in large United Kingdom (UK) primary care databases have demonstrated a 1.5fold increased risk of developing gout among patients with OSA [4,9] with the overall risk peaking 1 to 2 years after OSA diagnosis [9]. While both papers statistically adjusted their analyses for body mass index (BMI), type 2 diabetes mellitus, ischemic heart disease, hypertension, the use of diuretics of an unspecified class, and alcohol consumption, renal impairment was either ignored or considerably under-recorded [4].…”
Section: Introductionmentioning
confidence: 99%
“…Later, in 2018 Blagojevic-Bucknall et al [3], analyzed the data of 15879 patients with OSA (in comparison with 63296 controls), and found that the frequency of gout was almost twice as high in patients with OSA. A meta-analysis by Tingting Shi et al [1], published in 2019, included 18 independent studies and 157 607 patients (32395 with OSA, 125212 without OSA, of which 12 262 with gout).…”
Section: Literature Review 1 Population-based Studiesmentioning
confidence: 99%
“…Gout is one of the most common rheumatic diseases in the world, which affects about 1.14 % of the general population in China [1], and from 1.4 to 2.5 in other countries [2][3][4]. According to different sources, the incidence of OSA in the general population is 4-10 % [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation